2022
DOI: 10.1007/s12035-022-02782-x
|View full text |Cite
|
Sign up to set email alerts
|

HDAC3 Inhibition Stimulates Myelination in a CMT1A Mouse Model

Abstract: Charcot–Marie–Tooth disease (CMT) is the most common inherited peripheral neuropathy, with currently no effective treatment or cure. CMT1A is caused by a duplication of the PMP22 gene, which leads to Schwann cell differentiation defects and dysmyelination of the peripheral nerves. The epigenetic regulator histone deacetylase 3 (HDAC3) has been shown to negatively regulate myelination as well as its associated signaling pathways, PI3K-AKT and MAPK-ERK. We showed that these signaling pathways are indeed downregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
4
10
0
Order By: Relevance
“…To investigate the role PMP22 has in cholesterol and lipid metabolism in more detail, we focused on the less severe C3 CMT1A mouse model. These C3 mice present a dysmyelinating phenotype early in development followed by an improvement in myelination (Prior et al, 2022;Verhamme et al, 2011), similar to the aforementioned partial developmental amelioration in the cholesterol biosynthesis and lipid metabolism pathways (Fig. 1c, d).…”
Section: Pmp22 Overexpression Causes Abnormal Lipid Metabolism In The...supporting
confidence: 66%
See 2 more Smart Citations
“…To investigate the role PMP22 has in cholesterol and lipid metabolism in more detail, we focused on the less severe C3 CMT1A mouse model. These C3 mice present a dysmyelinating phenotype early in development followed by an improvement in myelination (Prior et al, 2022;Verhamme et al, 2011), similar to the aforementioned partial developmental amelioration in the cholesterol biosynthesis and lipid metabolism pathways (Fig. 1c, d).…”
Section: Pmp22 Overexpression Causes Abnormal Lipid Metabolism In The...supporting
confidence: 66%
“…Harboring at least 7 copies of the yeast artificial chromosome containing the human PMP22 gene, the C22 mice display postnatal defects in myelination (Robaglia-Schlupp et al, 2002;Robertson et al, 1999;Verhamme et al, 2011). The spontaneous revertant of the C22 mouse, designated the C3 mouse model (Verhamme et al, 2011) contains 5 copies of the human PMP22 gene, as we reported previously (Prior et al, 2022). These mouse models, in addition to the transgenic CMT1A rat model (Fledrich et al, 2012) are the current gold standard in vivo models for CMT1A research.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore, the participation of MAPK-ERK1/2 and PI3K-AKT signaling pathways are essential to the formation and differentiation of nerve myelination. 36 Also, enrichment was found in metabolism-related pathways, and it is noteworthy that bone metabolism markers (such as parathyroid hormone) were reported to be correlated with CSVD burden. 23 Generally, pathway analysis suggested hypoxia and inflammation response in brain as well as metabolic disorders were significantly regulated by these DE miRNAs.…”
Section: Discussionmentioning
confidence: 98%
“…It would be interesting in future studies to test different Theophylline treatment paradigms, such as longer-term treatments or several treatment rounds, to potentially further improve (re)myelination and functional recovery, and to test the efficacy of Theophylline treatment in other models of demyelinating peripheral neuropathies. A recent study showed that treatment with an HDAC3 inhibitor could also improve function and myelination in another CMT1A mouse model [ 51 ]. Since HDAC3 inhibition and HDAC2 activation by Theophylline treatment act through different pathways, it would be interesting to test whether a combination treatment could have additive or synergistic effects in the induction of (re)myelination and functional recovery in demyelinating peripheral neuropathies.…”
Section: Discussionmentioning
confidence: 99%